Rancang Bangun Kompor Lipat Portable Thermoelektric untuk Pecinta Alam: Design and Build a Portable Thermoelectric Folding Stove for Nature Lovers - sulistiyanto, sulistiyanto (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2023)
A portable stove is a very practical and efficient cooking device, used when camping, traveling, or as an alternative in an emergency. This stove is equipped with a thermoelectric stove, which can convert heat into electrical power. The young nature lovers of Randu Tata Village, when camping in the mountains, often experience running out of battery on their cellphones because on the mountain there is no place to charge the battery. Because of this, a stove was made, as well as being useful as a cellphone charger. By using a quantitative approach method. The aim of the research is to make a portable folding stove that can be used to charge cellphones. The discussion plan, in this discussion, will focus on how the output on the wall of the folding stove can later be converted into electrical power using thermoelectric, then the output can be used to charger cellphones. In this folding stove, the electrical power using a thermoelectric generator increases with increasing temperature, when the temperature is 39°C the thermoelectric output is 0.37 volts, and when the temperature is 100°C the thermoelectric output is 2.24 volts. From the 5V Step Up USB Converter connector installed next to the stove, it can be used to fill/charge power banks, cellphone batteries, and can also power lights.